Sociabilidades en las plazas de Buenos Aires. Usos, usuarios y diseño urbano - Egea Jiménez, Carmen; Salamanca Ospina, Edwar Leonardo (El Colegio de México A.C., 2020)
The article is part of a broader research on the analysis of public spaces and places from the approach of sociability, considering a theoretical-methodological reflection focused on three squares of Buenos Aires: Madero Harbour, Lavalle and Spain. Three analysis tools are used: the urban walk, the field notebook and the survey. Some results indicate that sociability is present in many ways in the three places; that people enjoy the space together with familiar people and in contact with strangers; that the use develops a creative spatial experience beyond the design; and that distance is not decisive for its use.